Exploring Lesson Learned From Lecturers’ Experience On Implementing Lesson Study In Higher Education - Syarifah, Eva Fitriani (Journal of English Language Learning, 2023)
In the ever-evolving landscape of education, the importance of innovative teaching methodologies cannot be overstated. One such approach that has gained substantial traction in recent years is Lesson Study. This study aims at investigating lecturers’ experience on implementing lesson study, specifically the lesson learned from lesson study. This study employed case study which involved five lecturers at higher education level as the participants. The data were gained through open ended questionnaire, interview, and documentation. The results indicated that the lessons learned that confirmed by the participants are: enhanced creativity and innovation, targeted student - centered teaching, cultivation of reflective practitioners, and building a supportive community. In conclusion, lesson study is not only gives new experience for lecturers but also new insight that can be useful for their teaching improvement.